The identity of Automeris ophthalmica Moore, 1883 (Lepidoptera: Saturniidae, Hemileucinae) - V. O. Becker (SHILAP, 2022)
The identity of Automeris ophthalmica Moore, 1883, sp. rev. is recognized, based on a specimen reared from a larva that matched the description and illustration of the one from which the female holotype was reared. This finding makes Pseudautomeris ophthalmica (Moore), the senior synonym of the following names: Automeris coronis Schaus, 1913, syn. n., Automeris parametea Bouvier, 1936, syn. n., and Automeris coronoides Bouvier, 1936, syn. n.